Correlation between the bleeding coagulation tests before vertebral surgery and the perioperative bleeding amount in geriatric patients using antiaggregants and anticoagulants - Yardimci, Bulent; Enercan, Meric; Hamzaoglu, Azmi; Reyhan Diz Kucukkaya; Bold, Nomin (Asian Journal of Medical Sciences, 2023)
Background: The world is witnessing an increase in its elderly population, which is reflected in the growing number of orthopedic surgeries being performed. With the increase in the number of major operations performed on the elderly, it has become crucial to manage bleeding effectively during vertebral surgery. The substantial use of antiaggregants and anticoagulants in elderly patients presents an increased risk of bleeding, resulting in increased morbidity and mortality rates if not well managed. Hence, it is essential to evaluate these patients thoroughly in the pre-operative period to minimize the risk of bleeding and improve patient outcomes. Aims and Objectives: The aims of this study were to research how effective the use of antiaggregants (AAs) and anticoagulants (oral anticoagulants [OAC] and low-molecular-weight heparin [LMWH]) is on operations and post-operative bleedings in surgery performed at our orthopedics clinic especially in the geriatric age group. Materials and Methods: This study was made retrospectively on 80 patients aged 65 years and over, who have undergone vertebral surgery on hospitalization at the Istanbul Florence Nightingale Hospital’s Orthopedics Clinic between the months of January 2017 and December 2019. Results: The rate of blood product utilization during surgery of those using prophylactic LMWH was statistically significantly higher in comparison to those not on prophylactic LMWH (P=0.034). There has not been determined any statistically significant difference in the means of the bleeding amount during the operation and post-operative bleeding. There has not been determined any statistically significant difference in the means of the bleeding amount during the operation and the post-operative period use and do not use any AA. Conclusion: In the geriatric group of age, which shall undergo vertebral surgery, it seems like an appropriate approach to discontinue AA and OAC 7 days before the operations. We have observed that the utilization of LMWH either for prophylactic purposes or for bridging purposes in the group using OAC does not significantly increase the bleeding probability.